Addition of sesamum indicum protein isolates improves the nutritional quality and sensorial attributes of wheat flour muffins - Sibt-e-Abbas, Muhammad; Sadiq Butt, Masood; Rafiq Khan, Moazzam; Shahid, Muhammad (Progress in Nutrition, 2018)
In the present research, efforts were made to enhance protein content of muffins using non-conventional protein sources. In this context, wheat flour was enriched with varying levels (5, 10, 15, 20 and 25%) of sesame protein isolates (SPI). Flour blends were used to prepare protein enriched muffins that were further evaluated for chemical composition, gross energy, color & textural analysis, and sensorial appraisal. The results were quite conclusive that nutritional quality of the muffins was improved with addition of SPI. Moreover, color analysis showed decreasing trend for L* & b* value, chroma and hue angle, while increasing trend was noticed for a* value. Likewise, the texture profile of muffins showed that firmness increased while elasticity decreased with gradual increase in protein contents. Sensory evaluation showed that muffins containing 15% SPI were rated better by the trained panelists. Conclusively, owing to high nutritive value and balanced nutritional profile, the use of sesame protein isolates can be handy tool to improve the nutritional quality of wheat based bakery products. These protein enriched products i.e. muffins can also help to fulfill the nutritional requirements of masses especially in developing countries.